Klasifikasi Kesegaran Ikan Menggunakan Citra Mata dengan Convolutional Neural Network Arsitektur VGG-16 - Ni Made Sri Ulandari; Resti Ajeng Sutiani; Rizal Adi Saputra (Program Studi Teknik Informatika, 2024)
Sea fish are the most widely consumed type of fish by households in Indonesia, serving as an important source of protein for the body. According to Matondang's (2022) study titled